Employee training and development / Raymond A. Noe - Noe, Raymond A.
The book reflects the latest “hot topics” in the area of training and development. Some of the new topics discussed in the book are the flipped classroom, microlearning, adaptive training, big data and workforce analytics, augmented reality (AR), artificial intelligence(AI), knowledge management, massive open online course (MOOCs), mobile learning (using smartphones), reverse mentoring, and unconscious bias training. Each chapter contains the most recent academic research findings and company practices.